2003
DOI: 10.1194/jlr.m200218-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Plasma fatty acids and [13C]linoleic acid metabolism in preterm infants fed a formula with medium-chain triglycerides

Abstract: Most preterm infant formulas contain mediumchain triacylglycerols (MCT), but the effects of MCT on polyunsaturated fatty acid status and metabolism are controversial. Thus, we studied the effects of MCT on linoleic acid metabolism using stable isotopes. Enterally fed preterm infants were randomized to receive for 7 days 40% of fat as MCT (n ‫؍‬ 10) or a formula without MCT (n ‫؍‬ 9). At study day 5, infants received orally 2 mg/kg body weight of 13 C-labeled linoleic acid. Fatty acids in plasma lipid classes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…FA10:0 is more likely to be esterified into triglycerides because FA10:0 esterified to phospholipids or cholesterols has not been detected in plasma. 40,42,43 This finding supports the hypothesis that during the oral loading of MCT, the hepatic clearance of MCFA remains incomplete. Therefore, unmetabolized MCFA may be esterified to triglycerides, packed into VLDL and released into the systemic circulation, as MCFA containing VLDL has also been detected following the MCT diet.…”
Section: Esterified Capric Acid Concentrationsupporting
confidence: 75%
“…FA10:0 is more likely to be esterified into triglycerides because FA10:0 esterified to phospholipids or cholesterols has not been detected in plasma. 40,42,43 This finding supports the hypothesis that during the oral loading of MCT, the hepatic clearance of MCFA remains incomplete. Therefore, unmetabolized MCFA may be esterified to triglycerides, packed into VLDL and released into the systemic circulation, as MCFA containing VLDL has also been detected following the MCT diet.…”
Section: Esterified Capric Acid Concentrationsupporting
confidence: 75%
“…As several studies indicate that moderate doses are better than excessive loads, it will have to be examined which dose and food matrix offers the most benefits, and whether naturally occurring MCFAs at position sn-1,3 of a triglyceride molecule and MCT oils have the same effect. Another interesting aspect is whether MCFAs, due to their preferred oxidation, might ''spare'' polyunsaturated fatty acids from oxidation, as fatty acid tracer exhalation tests and serum fatty acid profiles in preterm infants (Rodriguez et al, 2003) and rats (Nagata et al, 2003) suggest.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that during MCT/LCT ingestion, carnitine palmitoyltransferase I is inhibited by the production of malonyl-CoA, and consequently oxidation of long-chain fatty acids is reduced and their incorporation into complex lipids is enhanced (36). Indeed, we recently found reduced LA oxidation in preterm infants fed an enteral formula with 40% of fat provided by MCT compared with a 100% LCT formula (37). Even though the LCT emulsion provided approximately twice the amounts of palmitic acid (C16:0), TABLE n.d., not detected.…”
Section: Discussionmentioning
confidence: 99%